Housing Projects for Low-Income Groups and Modes of Economic Integration: A Comparative Study in Greater Cairo - Abouelmagd, Doaa; Kesteloot, Christian; Corijn, Eric (Tijdschrift voor Economische en Sociale Geografie (Journal of Economic & Social Geography), 2013)
The housing of low-income groups in Greater Cairo has always been difficult. However, the general shortage in housing supply is contrasting with the low occupancy rate of newly constructed public housing units. In contrast, despite their bad living conditions, informal settlements have a high occupancy rate. In order to analyse the reasons behind this contradiction, the paper compares four neighbourhoods ranging from formal and semi-informal to informal housing production and including one rehabilitation project. The livelihood conditions in each settlement are unravelled with the concept of modes of economic integration from Polanyi. For this purpose, semi-structured interviews were conducted and analysed with correspondence analysis. The findings indicate a preference among low-income groups for informal settlements because of three reasons: the advantages of geographical location, the nature of social networks and the strength of private redistribution systems, thus enabling an easier access to means of existence. The results and recommendations are further discussed in the paper.
Archetecture; Environmental Science
Keywords: Egypt; Greater Cairo; housing rehabilitation; informal settlements; livelihood; living conditions; low-income housing; modes of economic integration; occupancy rates; poor people; public housing; redistribution; squatter settlements

The Dialectics of Design - Jenkins, Barbara (Space & Culture, 2006)
The popularity of deconstructivist architecture around the world has invited controversy over the sensationalist design of these buildings. New urbanists, in particular, have criticized decon architecture as alienating and disorienting. From a historical perspective, this opposition between deconstructivists and new urbanists is the latest in a long line of debates over what constitutes "good design." Using a political-economy approach based on the work of Karl Polanyi, this article examines a centuries-long dialectic in design ideology between those who seek to embed design in social mores and those who attempt to "disembed" it from oppressive discourses. This analysis shows that the dialectic of design movements is intintately connected to the development of capitalist markets.
Architecture; Political Science
Keywords: capitalism; cities & towns; cultural studies; deconstructivism; deconstructivism (architecture); dialectic; disembeddedness; embeddedness; good design; modern architecture - 20th century; new urbanism; political economy